Arthritis associated with hidradenitis suppurativa. Issue 1 (January 1994) - Bhalla, R; Sequeira, W
Abstract : OBJECTIVE–To review the presentation and clinical findings of arthritis associated with hidradenitis suppurativa. METHOD–Medical records from the rheumatology clinics of two major teaching hospitals were reviewed for arthritis and hidradenitis suppurativa. The nine patient records fulfilling these criteria were reviewed and compared with 20 previous reports. RESULTS AND CONCLUSION–The arthritis associated with hidradenitis suppurativa is rare and most commonly affects the peripheral joints. The axial skeleton is less frequently involved and is often asymptomatic.